2021
DOI: 10.1371/journal.pmed.1003786
|View full text |Cite
|
Sign up to set email alerts
|

The blood metabolome of incident kidney cancer: A case–control study nested within the MetKid consortium

Abstract: Background Excess bodyweight and related metabolic perturbations have been implicated in kidney cancer aetiology, but the specific molecular mechanisms underlying these relationships are poorly understood. In this study, we sought to identify circulating metabolites that predispose kidney cancer and to evaluate the extent to which they are influenced by body mass index (BMI). Methods and findings We assessed the association between circulating levels of 1,416 metabolites and incident kidney cancer using pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 69 publications
(95 reference statements)
6
19
0
Order By: Relevance
“…An inverse association was previously reported between lysoPC a C18:2 with T2D in different studies 7,46 as well as with risks of breast, colorectal and prostate cancers in the pan-cancer analysis conducted in the EPIC Heidelberg study 25 . Our results regarding the three clusters of phosphatidylcholines were in line with many previously reported inverse associations between cancer and phosphatidylcholines 11,12,15,16,20,47 . Besides, we identified a positive association between the cluster that included PC aa C28:1 and cancer risk across all studied cancer types.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…An inverse association was previously reported between lysoPC a C18:2 with T2D in different studies 7,46 as well as with risks of breast, colorectal and prostate cancers in the pan-cancer analysis conducted in the EPIC Heidelberg study 25 . Our results regarding the three clusters of phosphatidylcholines were in line with many previously reported inverse associations between cancer and phosphatidylcholines 11,12,15,16,20,47 . Besides, we identified a positive association between the cluster that included PC aa C28:1 and cancer risk across all studied cancer types.…”
Section: Discussionsupporting
confidence: 93%
“…Glutamine was inversely associated with overall cancer risk in our analysis, while glutamate, a metabolite of glutamine, was positively related to the risk of all cancer types except for breast cancer. Although prior studies of the French E3N and SU.VI.MAX cohorts reported a positive association between glutamine and premenopausal breast cancer 51,52 , our results regarding glutamine and glutamate were consistent with those of many previous studies that reported inverse associations between glutamine and risk of colorectal cancer 18 , HCC 19,53 and T2D 7,54 , and positive associations between glutamate and risk of premenopausal breast cancer 52 , kidney cancer 15 , HCC 19,53 , as well as T2D 7 . Lower serum levels of glutamine were also observed in kidney cancer 55 and ovarian cancer 56 cases compared to controls.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Sensitivity and specificity of the clinical stage prediction model were 88.5% and 75.4%, respectively, with an AUC of 0.837 [ 135 ]. Guida et al, studied the first comprehensive metabolomics analysis of incident RCC to be conducted using a prospective design, using pre-diagnostic blood samples from up to 1305 RCC case–control pairs from five prospective cohort studies [ 136 ]. In this study, 25 metabolites were found to be robustly associated with risk after 1416 metabolites associated with the development of RCC were analyzed.…”
Section: Secondary Preventionmentioning
confidence: 99%